Evaluación de la Transformada de Hilbert en Señales Fonocardiográficas Fetales para la Generación de Cardiotacogramas - Jiménez González, A.; Charleston Villalobos, S.; Peña Castillo, M. A.; Aljama Corrales, A. T.; Ortiz Pedroza, M. R. (Revista Mexicana de Ingenieria Biomedica, 2018)
This paper demonstrates that the Hilbert transform is a suitable method to obtain time references from heart sounds (S1 and S2) to produce reliable fetal cardiotachograms (CTG). Fetal phonocardiograms were simulated with different SNR. The simulated signal envelopes were obtained through three different methods: The Hilbert transform, the absolute value of the differentiated signal and the absolute value. To evaluate the sensitivity of each envelope-generating method to SNR changes, the false positive (FP), false negative (FN), and the precision of the detected beginning, ending and maximum of the envelope corresponding to each heart sound was determined. The results show that the Hilbert transform produces the minimum number of FP and FN, and the detection of the beginning and maximum of the envelope corresponding to S1 are suitable points to generate reliable CTGs.